Comparative Analysis Spindle Speed Constant with Cutting Speed Constant against Surface Roughness Gradual Turning Steel ST 37 on the NC PU 2A Machine - Efendi, Defindo; A, Yufrizal; K, Arwizet (Universitas Negeri Padang, 2018)
Parameters of spindle speed and cutting speed affect surface roughness in the turning process. The purpose of this research is to know the comparison of the level surface roughness resulting from the parameters of spindle speed constant and cutting speed constant. The method of this research is experimental research, by performing gradual turning process on the steel ST 37 specimens in the NC PU 2A EMCOTURN 120 machine. The number of specimens is 6 specimens, each specimen is gradual turned as much 3 levels, each level is tested as much 3 points of surface quality using